2013
DOI: 10.1097/bsd.0b013e31824c7d22
|View full text |Cite
|
Sign up to set email alerts
|

Stand-alone Cervical Cages Versus Anterior Cervical Plate in 2-Level Cervical Anterior Interbody Fusion Patients

Abstract: The use of cage and plate construct in 2-level ACDF results in a shorter fusion duration and a lower subsidence rate than that of cage alone; however, there is no significant difference in the postoperative global and segmental alignment and clinical outcomes between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 13 publications
2
39
1
Order By: Relevance
“…In both groups a subsidence effect and loss of lordosis was measured, with a significantly greater effect in the group without APF. These results are consistent with those from other studies [17,11]. The greater preservation of segmental height and lordosis in the APF group might be due to stabilization of the operated segments within the first weeks after surgery while the autologous fusion was progressing.…”
Section: Anterior Plate Fixation Versus Stand-alone 2-level Acdfsupporting
confidence: 92%
See 3 more Smart Citations
“…In both groups a subsidence effect and loss of lordosis was measured, with a significantly greater effect in the group without APF. These results are consistent with those from other studies [17,11]. The greater preservation of segmental height and lordosis in the APF group might be due to stabilization of the operated segments within the first weeks after surgery while the autologous fusion was progressing.…”
Section: Anterior Plate Fixation Versus Stand-alone 2-level Acdfsupporting
confidence: 92%
“…Similar to previously published studies [19] our data showed that the use of a cage was superior to autologous bone in terms of restoration and preservation of disc height; also in accordance with the literature [11], we showed that APF was superior to a stand-alone technique. The effect of adding a plate was significantly more marked in the autologous bone group than in the cage group showing the importance of adding APF in this subgroup to guarantee preservation of disc height.…”
Section: Determinants Of Radiographic and Clinical Outcome After 2-lesupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, they show in combination with anterior plating excellent results in regard of the rate and quality of fusion. 12 Therefore, is seems questionable why for a comparable radiological result an absorbable cage should be used instead, which additionally has a much higher price compared with a standard PEEK cage.…”
Section: Discussionmentioning
confidence: 99%